ANTIMICROBIAL ACTIVITY OF NUTMEG (Myristica fragrans Houtt) FRUIT METHANOL EXTRACT AGAINST GROWTH Staphylococus aureus AND Escherichia coli - Nurhasanah Nurhasanah (UNIVERSITAS KHAIRUN, 2014)
Nutmeg (Mirystica fragrans Houtt) were one of famous spices comes from North of Mollucas. Nutmeg have many important part of itself for economic value especially it mace and seed but it fruit mostly unusefull. Chemical compounds whithin nutmeg fruit such atsiri oil have a promising component as an antimicrobial compound. The aim of this research were to determine antimicrobial activity and minimum inhibition concentration of nutmeg fruit againts growth of Staphylococus aureus and Escherichia coli by using metanol as a solvent. The study were conducted at PMIPA FKIP laboratory of Khairun Univercity. This was an experimental research by using completed randomized design which consist of fifteen concentration with three replication. Statistical analizing showed that Fhit Ftab (61,91) for S.aureus whereas 3, 81 for E.coli after applying methanol extract of nutmeg fruit for those bacterial growth, respectively. Neither for minimum inhibition concetration, S.aureus have a low MIC value (8%) than E.coli (10%), respectively). In conclusion extract of nutmeg fruit by using methanol had ability to inhibit the growth of S.aureus dan E.coli with MIC of S.aureus lower than MIC of E.coli.